Understanding Spanish Jihadist Terrorism: The Ideology Behind the Metaphors - López, Carlos Yebra (Routledge critical terrorism studies, 2025)
This book offers the first systematic account in English of the Spanish mass press coverage of jihadist terrorist' attacks in contemporary Spain. Drawing upon a critical analysis of the Spanish Transition to Democracy' (1975-82) and War on Terror' narratives, it examines the ideology underlying the metaphors used in the Spanish mainstream press coverage of the terrorist attacks in Madrid (2004) and Barcelona (2017). The book shows how these metaphors were systematically deployed for propagandistic purposes that sought to manufacture the consent' of the Spanish population while obstructing public deliberation apropos the attacks, strengthening Spanish democracy' by defining it in opposition to jihadist terrorism.' This book will be of interest to students of Critical Terrorism Studies, Spanish Politics, Media Studies, and Security Studies. Chapter 7 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license